Are blackout days free of charge? Valuation of individual preferences for improved electricity services - Raul Jimenez M. (Inter-American Development Bank (IDB), 2017)
Low-quality infrastructure services are persistent in developing countries, a situation mainly affecting the poorest households in contexts of high rates of informal access and heavily subsidized services. This paper exploits choice experiments, specifically designed for formal and informal users, to examine whether households in this situation are willing to pay for electricity service improvements. The analysis takes place in urban Dominican Republic, a country with one of the highest rates of electricity theft and lowest quality of services. The results strongly indicate that households value service improvements, showing average willingness to pay around US9 for informal users, and 22 percent for formal users with service deficiencies. The estimated valuations are significantly heterogeneous across households, and such variance is mainly explained by household income, satisfaction with the electricity service, and household characteristics, such as family size and dwelling size. These results indicate substantial welfare losses derived from low-quality electricity services equivalent to over 35 percent of the direct fiscal subsidy to the utilities.
Keywords: C25; C93; D12; Q41; 330; Willingness to pay; Choice experiments; Hypothetical bias; Stated preferences; Mixed logit; Quality of electricity services; Electricity subsidies; Informal electricity access